(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
In this paper, the authors extend and generalize some results of previous workers to completely semiprime G-rings. If U is an admissible Lie ideal of a completely semiprime G-ring M, d is a (U, M)-derivation of M and f is a generalized (U, M)-derivation of M then under some suitable conditions, workers prove that f(uav) = f(u) av + uad(v) holds for all u, v Î U and a Î G. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 115-123, 2015